MUSIC IN VIRTUAL REALITY: NEW OPPORTUNITIES FOR COMPOSERS AND PERFORMERS - Akmaljon Yuldashev (Journal of Learning on History and Social Sciences, 2024)
Virtual reality provides the opportunity to experience unique visual and audio experiences that directly impact our senses. A virtual reality headset allows you to create the feeling of being in another world or situation, opening up new horizons for exploration and creativity. When we talk about music in virtual reality, it means that the sound elements become an integral part of the simulated environment. Music can complement visuals and help create a more complete and engaging virtual experience for the user.